Tissue distribution and targeting evaluation of TMP after oral administration of TMP-loaded microemulsion to mice. (December 2013) - Ma, Li; Fan, Yanni; Wu, Hongfei; Na, Sha; Wang, Lei; Lu, Chuanhua
Abstract : The aim of this study was to quantify the oral delivery systems of Tetramethylpyrazine Microemulsion (TMP ME) to heart, liver, spleen, lung, kidney and brain by comparing TMP level after oral administration at a dose of 100 mg kg −1 with those of TMP tablet suspension (TMP SWW). This study was taken in mice to develop a suitable analytical methodology in pharmacokinetics studies and to manipulate the tissue distribution and targeting evaluation. Drug concentrations in tissues were determined at different times post-mortem. An HPLC method for separation and quantification of TMP was developed and validated by studying mice tissues. Following oral administration, TMP concentrations in different tissues were constantly detected for quite a long time and finally differed significantly from each other. The AUC rank order 3 of ME group is AUCliver  > AUCbrain  > AUClung  > AUCspleen  > AUCheart  > AUCkidney, while the SWW group is AUCliver  > AUClung  > AUCspleen  > AUCheart  > AUCbrain  > AUCspleen . Especially, the AUC value in brain region (AUCbrain ) of ME is 6.06-fold of SWW. The drug relative overall targeting efficiency (RTE) are calculated: heart (7.49%), liver (3.54%), spleen (12.60%), lung (6.02%), kidney (2.86%) and brain (12.51%). The results from ME directly showed obvious targeting transport to the brain. These results indicated that this new family of pharmaceutical carriers can be used for the solubilization and targeted delivery of poorly soluble drugs to various pathological sites in the body.